GluN2B-containing NMDA receptor attenuated neuronal apoptosis in the mouse model of HIBD through inhibiting endoplasmic reticulum stress-activated PERK/eIF2α signaling pathway - Wu, Mengxue; Xu, Shilian; Mi, Kai; Yang, Shuang; Xu, Yuanyuan; Li, Jie; Chen, Junyang; Zhang, Xiaomin (Frontiers in Molecular Neuroscience, 2024)
Introduction Neonatal hypoxic-ischemic brain damage (HIBD) refers to brain damage in newborns caused by hypoxia and reduced or even stopped cerebral blood flow during the perinatal period. Currently, there are no targeted treatments for neonatal ischemic hypoxic brain damage, primarily due to the incomplete understanding of its pathophysiological mechanisms. Especially, the role of NMDA receptors is less studied in HIBD. Therefore, this study explored the molecular mechanism of endogenous protection mediated by GluN2B-NMDAR in HIBD. Method Hypoxic ischemia was induced in mice aged 9-11 days. The brain damage was examined by Nissl staining and HE staining, while neuronal apoptosis was examined by Hoechst staining and TTC staining. And cognitive deficiency of mice was examined by various behavior tests including Barnes Maze, Three Chamber Social Interaction Test and Elevated Plus Maze. The activation of ER stress signaling pathways were evaluated by Western blot. Results We found that after HIBD induction, the activation of GluN2B-NMDAR attenuated neuronal apoptosis and brain damage. Meanwhile, the ER stress PERK/eIF2α signaling pathway was activated in a time-dependent manner after HIBE. Furthermore, after selective inhibiting GluN2B-NMDAR in HIBD mice with ifenprodil, the PERK/eIF2α signaling pathway remains continuously activated, leading to neuronal apoptosis, morphological brain damage. and aggravating deficits in spatial memory, cognition, and social abilities in adult mice. Discussion The results of this study indicate that, unlike its role in adult brain damage, GluN2B in early development plays a neuroprotective role in HIBD by inhibiting excessive activation of the PERK/eIF2α signaling pathway. This study provides theoretical support for the clinical development of targeted drugs or treatment methods for HIBD.